PERANAN DAN TANGGUNG JAWAB NOTARIS DALAM PEMBAGIAN HARTA BERSAMA BERDASARKAN PUTUSAN NOMOR 300/PDT.G/2020/PA BTA - Aditya Minang Prima; Heru Susetyo (Program Magister Ilmu Hukum Universitas Pancasila, 2021)
This paper discusses the distribution of joint assets after the end of marriage and the Roles and Responsibilities of Notaries in Sharing Collective Assets Based on Decision Number 300 / Pdt.G / 2020 / Pa Bta. Article 35 of the marriage law states that joint property is property that is obtained during marriage, which means assets obtained from the beginning of the marriage until the end of the marriage. In this case, the distribution of joint assets should be carried out immediately after the end of the marriage between husband and wife so that there is no legal action on one party regarding the joint property. This research is normative. The result of this research is that the joint assets that have not been distributed to the wife as the plaintiff and the husband as the defendant have taken legal action on the joint property by reversing the name of deed No. 29 without the knowledge of the wife and the judge decided that the distribution of the assets was carried out equally between the wives. and husbands based on article 37 of law No. 1 of 1974 jo Article 97 compilation of Islamic law. In the transfer of rights to deeds, there are conditions that must be met by the tappers such as having the consent of the wife, in this case the notary has been negligent because deed by checking all the conditions that must be met by the applicant and the notary's responsibility for deed no 29, namely to cancel the deed because deed no 29 is legally flawed